An Assessment of Social Media Opportunities in Public Relations Practice at University K and St Paul Universities in Kenya - Nyabera, Samwel; Mwita, James Marwa (Journal of Communication and Public Relations, 2025)
To ensure adequate public relations in the 21st Century, universities have turned to Social Media in service delivery. Despite the availability and utilization of social media tools, there is still limited understanding of the social media possibilities, especially WhatsApp, Facebook, and Twitter, that private universities in Kenya have not fully harnessed for public relations. This study evaluates the public relations social media opportunities that University K and St. Paul Universities in Kenya have not yet taken advantage of. This research took place from May to July 2022. A mixed methods approach was employed, incorporating a questionnaire and interviews. It involved 270 questionnaire respondents and two in-depth interviews with PR officers from the two selected universities. Quantitative data were analyzed using SPSS v. 23, while qualitative data were analyzed using narrative analysis. The results indicated that social media positively affected service delivery within the Public Relations departments. It was also disclosed that social media aided in promoting their accomplishments, improved information quality, established a user-friendly platform for the public to interact with their organization, increased access to information, and strengthened the organization’s lobbying capacity for public backing of their stances. The research suggests that universities should take advantage of the ample opportunities social media offers to engage with their audiences and assist organizations in expanding their reach for public relations efforts.